First downhole sampling of a natural hydrogen reservoir in Colombia - Patiño, Cesar; Strąpoć, Dariusz; Torres, Oscar; Mullins, Oliver; Bustos, Ulises; Bermudez, Oscar; López, Albeiro; Trujillo, Maria; Morales, Hans (Frontiers in Energy Research, 2024)
In Colombia, natural hydrogen (H2) was recently declared a source of unconventional renewable energy. An opportunity has been recognized to take advantage of information on the infrastructure of oil fields as a springboard for H2 exploration in the country’s sedimentary basins. Establishing similarities and identifying components of the possible H2 systems in the different geological contexts where the presence of H2 has been proven in Colombia’s sedimentary basins allows the establishment of the probability of H2 in the Ecopetrol oil and gas fields in Colombia. The components of H2 systems include potential H2 source rocks and reservoirs. Potential accumulations need to be confirmed through measurements, sampling, and well testing. The main types of H2 well exploration carried out in this study resemble those in oil fields and include surface surveys, logging while drilling (mud gas and petrophysics), and downhole sampling. In the case of a hydrocarbon field in the Llanos Basin, a detailed seismic and geological review, supported by surface survey indications of H2 traces, prompted further investigation while drilling wells in the basin to establish the provenance and distribution of H2. Based on the proposed workflows, we evaluated possible strategies in the area. Given the positive evaluation of the possible elements of a theoretical H2 strategy, a sampling plan was defined both in the well and on the surface that will reduce the uncertainty of the prospect of natural H2 in the studied basin but may also be applied to similar geological settings worldwide. This study shows the application of such an H2 exploration strategy, leading to the presented results from the first well and confirming the presence of an active natural H2 system in the Llanos Basin.